Sensitivity of RSUP Dr Sardjito's Covid Score to Positive PCR Swab Test Results as A Diagnostic Tool - Eko Budiono; Tri Indriaswati (Asian Journal of Social and Humanities, 2023)
Coronavirus disease 2019 (COVID-19) is a newly discovered disease that has spread throughout the world so that it isconsidered a pandemic. Effective initial screening in patients is important to determine the need for diagnostic and therapeutic measures. Until now, there have been no screening tools that have been designated as gold standards so that RSS was developed based on the manifestation of COVID-19 as an early scoring tool. Assess the sensitivity of RSS scoring to comfirmed PCR COVID events. A case control study was conducted on patients from March to April 2021 at RSUP dr. Sardjito. A total of 50 respondents were randomly screened using RSS tools and confirmed with PCR. Then the prevalence of positive cases is calculated based on RSS scoring with patients who are positive based on PCR of the 50 respondents examined, 45 people were declared confirmed with COVID-19. The number of patients with high probable criteria who confirmed COVID-19 was 37 people. The number of patients with moderate probable criteria who confirmed COVID-19 was 9 people. Based on the formula, the sensitivity of RSS to confirmed COVID-19 is 97.72%. Dr Sardjito's SOP r scoring sensitivity to confirmed COVID-19 was 97.72%. Thus, Dr Sardjito's SOP r scoring sensitivity to confirmed COVID-19 was 97.72%. Thus, Dr. Sardjito's Covid R SUP Scoring can be used as a tool to assess high risk confirmed COVID-19 patients in early screening.